Saisir la position sémio-spatiale d’un élément géographique dans les cartes cognitives - Kevin Clementi; Thierry Ramadier (M@ppemonde)
This paper proposes an analysis of the semio-spatial position of a geographical element, in this case, a state border, in the cognitive maps of a border town. On the theoretical level, the use of the semiological concept of topos and the notion of position allow us to grasp the meaning of a geographical element with regard to social positions, in order to identify their contribution to the positioning of the element in the cognitive map. Methodologically, this analysis calls for the thight integration of a discursive task within the more classical methods of cognitive mapping.